α-Glucosidase inhibitor activity of endophytic fungi isolated from oil palm leaves (Elaeis guineensis Jacq) - Harmileni, Harmileni; Tarigan, Ratna Kristina; Barus, Adil; Rosmiati, Rosmiati; Silvany, Rika (Jurnal Prima Medika Sains, 2025)
Indonesia ranks seventh globally in diabetes prevalence, with an estimated rate of 4.8%, and more than half of the cases remain undiagnosed. By 2030, the number of individuals with diabetes in Indonesia is projected to reach 21.3 million. Alpha-glucosidase inhibitors are commonly used to prevent the progression of prediabetes; however, their use is often associated with adverse side effects. Therefore, research is needed to identify natural sources of alpha-glucosidase inhibitors. This study aimed to evaluate the in vitro alpha-glucosidase inhibitory activity of endophytic fungi isolated from oil palm leaves. The research consisted of fungal isolation, microscopic characterization, and analysis of α-glucosidase inhibitory activity. Two pure endophytic fungal isolates, designated JES1 and JES2, were successfully obtained. Isolate JES1 exhibited a denser mycelial network with well-defined septation, whereas JES2 displayed loosely arranged, curved hyphae, suggesting that the variation was likely due to differences in growth phase or sampling location rather than taxonomic divergence. Microscopic observations identified JES1 and JES2 as Colletotrichum sp. and Fusarium sp., respectively. The α-glucosidase inhibitory assay showed that isolates JES1 and JES2 demonstrated inhibitory activities of 79.4% and 20.8%, respectively, while the positive control, acarbose, exhibited an activity of 81%. These results indicate that endophytic fungi isolated from oil palm leaves have potential as natural sources of bioactive compounds with α-glucosidase inhibitory properties.